Development of a building information modelling (BIM) migration path model for construction professionals - Brahim, Juliana (2018)
The construction professionals have the notion that by implementing Building Information Modelling (BIM) in construction could overcome problems such as delay, cost overrun, clashes in project design and undesirable quality in construction. However, they failed to take the advantages of the BIM benefit as they are still trying to find the best way to take on board the BIM into current practices. Most of the professionals do not know ‘when’ and ‘how’ to apply BIM throughout the construction lifecycle. Several research models related to BIM has been developed to improve and encourage BIM implementation. Nevertheless, the developed models have limitations in highlighting the steps involved that could assist the construction professionals in implementing BIM effectively in Malaysia. Therefore, this research is aimed to develop a model that would be able to assist Malaysian construction professionals in implementing BIM in a structured way. A semi-structured interview was carried out with respondents that have various experienced and currently involved in BIM projects in the Malaysian construction industry. Findings show that the construction professionals are lacking in knowledge and experience in using BIM in various stages of construction. Thus, they were unable to fully capitalise the benefit of 3D models. Migration path model was proposed and evaluated as a strategic approach for BIM implementation in the Malaysian construction industry. The identification of five (5) activities (BIM Awareness, Develop BIM Strategy, Implement BIM, Monitor BIM and Expand BIM Implementation) with the three (3) enablers (BIM work contract, BIM work process and BIM technology) in the model is expected to be able to assist construction professionals to implement BIM with the right BIM concept and later, the benefit could be obtained for improving construction project. The proposed model could be as a guideline for construction professionals in implementing BIM, specifically in countries that new in BIM. The model is also expected to be able to fill the gap in BIM implementation by supporting the initiatives by the Malaysian government for increasing productivity in construction projects by using new technology like BIM.